Evaluación y caracterización fisicoquímica de vino de frutas arándano (vaccinium myrtillus) y mora (rubus ulmifolius) y su incidencia en la calidad sensorial. - Ribadeneira Padilla, Joseph Xavier (2022)
Ecuador, due to its geographical location is not traditionally known for the grape wine production, but for this same characteristic is a several fruits producer, whose can make fruit wine. The actual work focuses onto the making fruit wine, blueberry and blackberry, with the aim to assess the physicochemical characteristics and the impact about sensory quality. It was used a completely randomized block design into a 2x2x2 factorial arrangement, by being factor A the fruit concentration; factor B, yeast activation temperature and factor C, soluble solids concentration, each factor with two levels, with a 8 treatments total. Into the fruit wine production soluble solids assessment (10.25°Bx); pH (3.14) and alcohol (9.55%), it was determined, which for soluble solids and alcohol, it is significant, in pH terms, it is not significant. The same way, it was assessed sensory quality into three phases: visual, olfactory and gustatory. The best treatment for the physicochemical characteristics, sensory quality and greater acceptability is the t6 treatment (50%blueberry-50%blackberry/35°C/23°Bx), by proceeding to perform the certified physicochemical analyzes into an external laboratory according to with the NTE INEN 374. Alcohol 9.62%; Total acidity 6.82 g/l; Volatile acidity 0.27 g/l; Total sulfur dioxide 676.56 mg/l; Methanol 63.46 mg/l and Sugar content 39.4 g/l. For sensory quality, it was determined into the visual phase, what it has a medium dark color; into the olfactory phase the primary odor is fruity, the secondary odor is to fermentation and the taste phase has a medium intensity, medium body, good harmony and long persistence.